2022
DOI: 10.1002/jmv.28050
|View full text |Cite
|
Sign up to set email alerts
|

Could red cell distribution width be used for predicting cardiac injury in neonates with COVID‐19?

Abstract: Background Coronavirus disease 2019 (COVID‐19) can affect people of all age groups and it can occasionally cause life‐threatening clinical illnesses in immunologically immature populations, especially in newborns. High red cell distribution width (RDW) values were used as an early prognostic biomarker of some neonatal diseases. We aimed to determine the prognostic value of RDW in severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) infected neonates. Methods New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The variations inherent in such illnesses have become more apparent; therefore, several clinical definitions have emerged. Overall, it is suggested that very few SARS-CoV-2-infected children suffer from MIS-C [ 59 , 78 , 79 ]. Among all pediatric MIS-C in 2 of the latter studies, some 1.7%–2.6% were <1 year of age.…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations inherent in such illnesses have become more apparent; therefore, several clinical definitions have emerged. Overall, it is suggested that very few SARS-CoV-2-infected children suffer from MIS-C [ 59 , 78 , 79 ]. Among all pediatric MIS-C in 2 of the latter studies, some 1.7%–2.6% were <1 year of age.…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
“…geogra phic regions and with now considerable cumulative numbers. 3,5,[9][10][11]13,[21][22][23][24]26,[30][31][32]34,41,45,46,48,[51][52][53][58][59][60][61][62] Table 1 details the more common disease features cited to date. Small case series, case reports, and reviews have mostly been consistent.…”
Section: Manifestations Of Infant Infectionmentioning
confidence: 99%